Regulation of autophagy and lipid accumulation under phosphate limitation in Rhodotorula toruloides - Wang, Ya-nan; Liu, Fang-jie; Liu, Hong-di; Zhang, Yue; Jiao, Xiang; Ye, Ming-liang; Zhao, Zong-bao Kent; Zhang, Su-fang (Frontiers in Microbiology, 2023)
Background: While it is known that autophagy is essential for cell survival under stressful conditions and it enables cells to overcome nutrient starvation. Inorganic phosphate (Pi) is an essential nutrient for cell growth and Pi-limitation can trigger autophagy and lipid accumulation in oleaginous yeasts, yet protein (de)phosphorylation and related signaling events response to Pi limitation and the molecular basis linking Pi-limitation to autophagy and lipid accumulation remain elusive. Results: Here, we compared the proteome and phosphoproteome of Rhodotorula toruloides CGMCC 2.1389 under Pi- limitation and Pi-repletion. In total, the proteome identified 3556 proteins and the phosphoproteome identified 1649 phosphoproteins contained 5659 phosphosites including 4499 pSer, 978 pThr, and 182 pTyr. We found Pi-starvation-induced autophagy was regulated by Autophagy-related proteins, not by the PHO pathway. When ATG9 was knocked down, the engineered R. toruloides strain produced significantly less lipids under Pi-limitation, suggesting that autophagy required Atg9 in R. toruloides and autophagy was conducive to lipid accumulation. Conclusions: Our results provide new insights into autophagy regulation under Pi-limitation and lipid accumulation in oleaginous yeast, which should be valuable to guide further mechanistic study of microbial oleaginicity and genetic engineering for advanced lipid producing cell factory.